2013
DOI: 10.1007/s12663-013-0519-2
|View full text |Cite
|
Sign up to set email alerts
|

Excision of Oral Leukoplakia by CO2 Lasers Versus Traditional Scalpel: A Comparative Study

Abstract: Through this study we can infer that CO2 laser supersedes conventional scalpel in terms of better intra-operative and reduced scarring. Post-operative pain and swelling after laser excision did not show any significant difference from that of scalpel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 12 publications
0
23
0
1
Order By: Relevance
“…In contrast, the CO2 laser by sealing blood vessels, lymphatics, and nerve endings, reduces to a minimum the local inflammatory response, which is related to lower levels of glucocorticoids, epinephrine and norepinephrine, and therefore to lower pain level. [5,8,9,21,22,27] Considering that skin is one of the tissues where the nociceptive system is most figurative, it is to be expected that the CO2 laser's ability to reduce stimulation of the skin nociceptive system may also be associated with a lower autonomic nervous system stimulation of the remaining tissues and organs to be operated upon, resulting therefore in discrete hemodynamic variations as registered in our study.…”
Section: Comparison Of the Hemodynamic Response In General Anesthesiamentioning
confidence: 57%
“…In contrast, the CO2 laser by sealing blood vessels, lymphatics, and nerve endings, reduces to a minimum the local inflammatory response, which is related to lower levels of glucocorticoids, epinephrine and norepinephrine, and therefore to lower pain level. [5,8,9,21,22,27] Considering that skin is one of the tissues where the nociceptive system is most figurative, it is to be expected that the CO2 laser's ability to reduce stimulation of the skin nociceptive system may also be associated with a lower autonomic nervous system stimulation of the remaining tissues and organs to be operated upon, resulting therefore in discrete hemodynamic variations as registered in our study.…”
Section: Comparison Of the Hemodynamic Response In General Anesthesiamentioning
confidence: 57%
“…Our study was not designed to evaluate the effect of the nature of the treatment. A comparative study with bilateral leukoplakia (one side of the lesion excised using CO2 laser and the other side using scalpel) has shown that advantages of laser include less bleeding intra operatively, less swelling and scarring post-operatively than scalpel ( 26 ). There was no significant difference in terms of post-operative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Three papers (9.9%) prospectively compared excision of OL by CO 2 laser versus traditional scalpel (Che et al, 2012;L opez-Jornet et al, 2013;Tambuwala et al, 2014). Table 4 summarizes these studies and the parameters used to compare the two methods (p > .05 was considered to be statistically significant).…”
Section: Comparative Studies Between Co 2 Laser and Cold Knife Surgerymentioning
confidence: 99%